2016
DOI: 10.1039/c5cc08034g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical properties of Li1.3Nb0.3V0.4O2 as a positive electrode material for rechargeable lithium batteries

Abstract: The binary system, xLi3NbO4-(1 - x)LiVO2, was first examined as an electrode material for rechargeable lithium batteries. The sample (x = 0.43) crystallizes into a cation-disordered rocksalt structure and delivers a reversible capacity of ca. 230 mA h g(-1), which originates from V(3+)/V(5+) redox with electrochemically inactive niobium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 23 publications
4
67
0
Order By: Relevance
“…Although pure Li 3 NbO 4 is electrochemically inactive, the substitution of 3 d transition‐metal ions for Nb/Li ions effectively induces conductive electrons as mentioned above ,. Such 3 d transition‐metal ions can accept electrons from oxide ions, leading to the activation of anionic redox coupled with cationic redox.…”
Section: Li3nbo4‐ and Li2tio3‐based Systems; Reversible And Irreversimentioning
confidence: 95%
“…Although pure Li 3 NbO 4 is electrochemically inactive, the substitution of 3 d transition‐metal ions for Nb/Li ions effectively induces conductive electrons as mentioned above ,. Such 3 d transition‐metal ions can accept electrons from oxide ions, leading to the activation of anionic redox coupled with cationic redox.…”
Section: Li3nbo4‐ and Li2tio3‐based Systems; Reversible And Irreversimentioning
confidence: 95%
“…Recently, Li-excess disordered (rocksalt) transition metal oxides (LEX-RS), such as Li 1.211 Mo 0.467 Cr 0.3 O 2 , Li 1.3 Mn 0.4 Nb 0.3 O 2 , Li 1.2 Mn 0.4 Ti 0.4 O 2 , and Li 1.2 Ni 0.333 Ti 0.333 Mo 0.133 O 2 , have gained much attention as a new class of high-capacity cathode materials, delivering capacities as high as 300 mAh g –1 412 . The surge of interest in these materials, previously thought to be inactive 1315 , is due to the realization that cation disorder can be tolerated as long as enough Li excess is present in the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Reversible capacity of electrode materials is potentially further increased by the enrichment of lithium contents with less transition metals in the close-packed structure of oxide ions. Recently, our group has reported that Li 3 NbO 4 (refs 20, 21) and Li 4 MoO 5 (ref. 22), which have higher lithium contents than those of Li 2 MnO 3 and Li 2 RuO 3 , are potentially utilized as host structures for a new series of high-capacity electrode materials.…”
mentioning
confidence: 99%